Deciding to Enter a Monetary Union : TheRole of Trade and Financial Linkages - Lama, Ruy (IMF Working Papers; Working Paper ;, 2012)
This paper evaluates the role of trade and financial linkages in the decision to enter a monetary union. We estimate a two-country DSGE model for the U.K. economy and the euro area, and use the model to compute the welfare trade-offs from joining the euro. We evaluate two alternative scenarios. In the first one, we consider a reduction of trade costs that occurs after the adoption of a common currency. In the second, we introduce interest rate spread shocks of the same magnitude as the ones observed during the recent debt crisis in Europe. The reduction of trade costs generates a net welfare gain of 0.9 percent of life-time consumption, while the increased interest rate spread volatility generates a net welfare cost of 2.9 percentage points. The welfare calculation suggests two ways to preserve the welfare gains in a monetary union: ensuring fiscal and financial stability that reduces macroeconomic country risk, and increasing wage flexibility such that the economy adjusts to external shocks faster.